Odpowiedź :
3(2x+9)=39
6x + 27 =39
6x = 39 - 27
6x = 12 / 6
x = 2
3(3x-2)=66
9x - 6 = 66
9x = 66 + 6
9x = 72/9
x = 8
2(4x-5)=14
8x - 10 = 14
8x = 14 + 10
8x = 24/8
x = 3
2(3+2x)=32
6 + 4x = 32
4x = 32 - 6
4x = 26/4
x = 13/2 = 6,5
6x + 27 =39
6x = 39 - 27
6x = 12 / 6
x = 2
3(3x-2)=66
9x - 6 = 66
9x = 66 + 6
9x = 72/9
x = 8
2(4x-5)=14
8x - 10 = 14
8x = 14 + 10
8x = 24/8
x = 3
2(3+2x)=32
6 + 4x = 32
4x = 32 - 6
4x = 26/4
x = 13/2 = 6,5
3(2x+9)=39
6x+27=39
6x=39-27
6x=12 /:6
x=2
3(3x-2)=6
2(4x-5)=14
2(3+2x)=32
6x+27=39
6x=39-27
6x=12 /:6
x=2
3(3x-2)=6
2(4x-5)=14
2(3+2x)=32